Perlindungan Hukum Hak Waris bagi Istri Tanpa Anak yang di Tinggal Mati Suami: Studi Kasus Kecamatan Lambu - Uswatun Hasanah; Muhamad Amin; Nasrullah (Jurnal Hukum Lex Generalis, 2026)
This study examines the legal protection of inheritance rights for childless wives whose husbands have passed away in Lambu Subdistrict. This study was conducted because there remains a discrepancy between the provisions of Islamic inheritance law and the actual practice of inheritance distribution in the community. The methods used were empirical legal research with a sociological approach and a case study approach. The results of the study indicate that the distribution of inheritance is still influenced by customs, family traditions and the dominance of the husband’s family, resulting in the wife’s rights often not being fulfilled fairly. Legal protection for the wife has not been optimally implemented due to the community’s limited understanding of the law and the weak enforcement of legal provisions in the practice of inheritance distribution within the community.